2015
DOI: 10.5114/pm.2015.49252
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical activity in preventing obesity in midlife women

Abstract: IntroductionObesity is one of the most common nutrition-related disorders worldwide and one of the major health problems in menopausal women, which significantly worsens the quality of life and can lead to severe diseases or even premature death. The aim of the study was to evaluate the relation between physical activity in different domains undertaken by menopausal women while performing daily activities and their body mass index (BMI).Material and methodsThe study was conducted on a random sample of 400 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…Age correlated inversely with the depression score, as has also been reported in other studies [33 -35]. BMI also correlated inversely with METs/week, as has also previously been reported [36,37]. There were no correlations between BMI and age in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Age correlated inversely with the depression score, as has also been reported in other studies [33 -35]. BMI also correlated inversely with METs/week, as has also previously been reported [36,37]. There were no correlations between BMI and age in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In this respect, it is interesting to point out that the present results indicated a lower level of physical activity (daily steps) in the overweight and obese groups. These results agree with those of a study involving women during menopause, which found an inverse relationship between the level of physical activity and BMI 22 . Levine et al 23 also observed a decline in walking with increasing body weight.…”
Section: Discussionsupporting
confidence: 83%
“…A study conducted on Polish women aged 45–55 showed that most women were moderately active in all IPA domains (work, transportation, leisure time and household) [41]. In that study, participants were not divided according to menopausal stage.…”
Section: Discussionmentioning
confidence: 99%